Atrophy and apoptosis in ventral prostate of rats induced by 5alpha-reductase inhibitor, epristeride - Qian Li-Hui; Wang Xiao-Lin; Tu Zeng-Hong (Acta Pharmacologica Sinica, 2016)
Aim: To study molecular mechanism of epristeride in the treatment of benign prostatic hyperplasia and discuss the possibility of using prostate acid phosphatase (ACP) as a marker of the atrophy of prostatic gland in vivo. Methods: Morphological changes in cells were observed by light microscope. TdT-mediated dUTP-biotin nick end labeling (TUNEL) technique and agarose gel electrophoresis were performed to detect the nucleosomal DNA fragmentation. The activity of pACP was also assayed. Results: Apoptosis occurred in both castration- and epristeride- treatment group. Both the degree and extent of apoptosis are much larger in the group of castration than that of epristeride-treated group. Both epristeride and castration decreased the prostate wet weight and DNA content but increased the prostate DNA concentration. Maximal or near maximal decreases were seen by d 10 in both groups. The activity of ACP was decreased by both castration and epristeride treatment. Changes in the ACP activity during treatment were coincide with other changes such as the prostate wet weight and DNA content. Conclusion: Apoptosis induced by epristeride was one of mechanisms in the treatment of benign prostatic hyperplasia and the activity of ACP could be used as a marker of prostate atrophy.